2020
DOI: 10.3390/biomedicines8100412
|View full text |Cite
|
Sign up to set email alerts
|

Native T1 Mapping Magnetic Resonance Imaging as a Quantitative Biomarker for Characterization of the Extracellular Matrix in a Rabbit Hepatic Cancer Model

Abstract: To characterize the tumor extracellular matrix (ECM) using native T1 mapping magnetic resonance imaging (MRI) in an experimental hepatic cancer model, a total of 27 female New Zealand white rabbits with hepatic VX2 tumors were examined by MRI at different time points following tumor implantation (day 14, 21, 28). A steady-state precession readout single-shot MOLLI sequence was acquired in a 3 T MRI scanner in prone position using a head-neck coil. The tumors were segmented into a central, marginal, and peritum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, the heterogeneity increased over time in 4T1 tumors, as reflected inter alia in a wider range and kurtosis of the histogram analysis and contrary, the heterogeneity of 67NR tumors as assessed with analysis of diffusion-weighted imaging did not increase during tumor progression. These features of tumoral composition correlate with native T1 times as well, which increase with the amount of necrotic areas and were thus higher in high malignant than low malignant tumors ( 48 ), as confirmed here. In the clinical setting examining patient with kidney tumors, native T1 times enabled to differentiate high grade clear cell renal cell carcinoma (cRCCs) from lower grade cRCCs ( 49 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the heterogeneity increased over time in 4T1 tumors, as reflected inter alia in a wider range and kurtosis of the histogram analysis and contrary, the heterogeneity of 67NR tumors as assessed with analysis of diffusion-weighted imaging did not increase during tumor progression. These features of tumoral composition correlate with native T1 times as well, which increase with the amount of necrotic areas and were thus higher in high malignant than low malignant tumors ( 48 ), as confirmed here. In the clinical setting examining patient with kidney tumors, native T1 times enabled to differentiate high grade clear cell renal cell carcinoma (cRCCs) from lower grade cRCCs ( 49 ).…”
Section: Discussionsupporting
confidence: 82%
“…In the clinical setting examining patient with kidney tumors, native T1 times enabled to differentiate high grade clear cell renal cell carcinoma (cRCCs) from lower grade cRCCs (49). The results also show the increase in T1 values during tumor progression (50), likely due to areas of dense proliferative undifferentiated tumor cells (51, 52) and increasing density of the extracellular matrix and collagen contents, assessed in a rabbit hepatic cancer model (48) and in specimens of breast cancer patients (53). However, in some studies, including a study evaluating the effect of anti-angiogenic therapy in a mouse ovarian cancer model, T1 times did not change during tumor growth (51).…”
Section: Discussionmentioning
confidence: 86%
“…Only a limited number of studies are available investigating the potential of plain T1 mapping to characterize tumors. Keller et al showed the potential of plain T1 mapping as a reliable non-invasive method for quantification and characterization of primary liver tumors in a rabbit model 23 . In our study, G3 tumors had a slightly higher mean T1 time than G1 and G2 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, on the basis of different T1 relaxation times in different tumor areas, T1-mapping MRI allows for the visualization of the tumor extracellular matrix (ECM) in a preclinical rabbit model of liver cancer (Fig. 8c; image 1,2) [300]. High T1 relaxation times in tumor and short T1 relaxation times in regions surrounding the tumor suggest native T1 mapping as a possible quantitative means to assess ECM remodeling.…”
Section: Imaging Fibrosis In Cancermentioning
confidence: 99%
“…Color-coding: the analysis of manuscripts described in section 4.2 reveal the frequency in which each organ and imaging modality are investigated and used for the detection of fibrosis in cancer; light red = low frequency; red = medium frequency; dark red = high frequency. All images were adapted with permission [300,302,303,309,312,314].…”
mentioning
confidence: 99%